Barriers and Facilitators of Simulation-Based Education in Stroke Nursing Management at a Regional Referral Hospital in Southwestern Uganda: A Qualitative Study - Josephine Nambi Najjuma; Francis Bajunirwe; Scovia Nalugo Mbalinda; Frank Ssedyabane; Gerald Mwebembezi; Shirley Moore; Mark Kaddumukasa; Esther C Atukunda (Advances in Medical Education and Practice, 2025)
Introduction: Simulation-based education (SBE) improves skills and knowledge among health professionals. Stroke nursing necessitates swift decision-making, elevated levels of clinical competence, and interdisciplinary collaboration. SBE improves these competencies but encounters implementation challenges. The objective of this study was to explore the barriers and facilitators of SBE implementation for stroke care for nurses at a referral hospital in Uganda. Methods: From March to July 2024, a descriptive qualitative study was carried out at Mbarara Regional Referral Hospital and Mbarara University of Science and Technology using focus group discussions (FGDs), and key-informant interviews (KIIs). The FGDs were carried out with nursing students. The KIIs participants included purposively selected nurses, nurse educators, and other health care providers involved in stroke care and bedside teaching. The study was guided by the Consolidated Framework for Implementation Research (CFIR) and used deductive thematic analysis to identify barriers and facilitators for simulation-based stroke education (SBSE). Results: We conducted 4 FGDs, and 12 KIIs. The FGDs participants’ mean age was 24 years and 36 years for other participants in KIIs. The barriers to SBSE included anticipated high cost for simulation methods, the anticipated high costs to translate lessons learned to real hospital setting, resistance to change from established routines. The high patient-to-nurse ratios and lack of stroke specific structured training are also barriers. The facilitators included strong institutional administrative support for simulation methodology, availability of training facilities at the simulation center, and prior exposure to simulation methodologies. Conclusion: Strong administrative support exists for SBSE. However, for successful implementation, there is a need to address the resource limitations, address anticipated resistance to change, and foster a culture of continuous learning and improvement within healthcare institutions. Future interventions should strategically address identified barriers while leveraging facilitators can enhance the success of SBSE stroke nursing care in resource-limited settings.
Keywords: Stroke; SOCIAL SCIENCES::Social sciences::Education; Simulation; Nurses; Uganda